Sustaining Sherpa language and culture in New York. Issue 1 (1st August 2019) - Sherpa, Pasang Yangjee
Sherpas moved from their original homeland in Solukhumbu district of Nepal to adjacent mountain districts and later to urban centres such as Kathmandu and Darjeeling over several generations. By the end of the twentieth century, many had also moved permanently to North American and European countries. Now, after Kathmandu in Nepal, the largest concentration of Sherpas can be found in Queens, New York, and the surrounding boroughs. The case of New York Sherpas is unique because for the first time in history, thousands of Sherpas from different parts of the Himalayas are living together and sharing a new home. Earlier, these Sherpas were separated for generations by geographic obstacles, great distances and international boundaries. Although the process of adapting to a new sociocultural environment is not novel, this article argues that the kinds of challenges and opportunities that New York has presented for the Sherpas are different from their experience elsewhere.Sherpas are acutely aware of the risk of losing their language and culture in their new homes in the United States, especially when it comes to transmitting cultural knowledge to the next generation. Many are therefore actively involved in the preservation of their language and culture through community mobilization in the form of kyidugs.1 Based in different cities across the United States, Sherpa kyidugs uniformly emphasize the significance of promoting their language and culture within the community. A shared place of worship and gathering is key to Sherpas' efforts to preserve and practice their culture, and so the kyidugs recognize the need for a community building, where they can gather to perform religious rituals and festivals, offer language classes or simply gather.